The role of nitric oxide in regulation of the cardiovascular system in reptiles - Skovgaard, N.; Galli, G.; Abe, Augusto Shinya [UNESP]; Taylor, E. W.; Wang, T. (Elsevier B.V., 2005)
The roles that nitric oxide (NO) plays in the cardiovascular system of reptiles are reviewed, with particular emphasis on its effects on central vascular blood flows in the systemic and pulmonary circulations. New data is presented that describes the effects on hemodynamic variables in varanid lizards of exogenously administered NO via the nitric oxide donor sodium nitroprusside (SNP) and, preliminary data on the effects of SNP inhibition of nitric oxide synthase (NOS) by L-nitroarginine methyl ester (L-NAME). Furthermore. on hemodynamic variables in the tegu lizard are presented. The findings are compared with previously published data from Our laboratory on three other species of reptiles: pythons (Skovgaard, N., Galli, G., Taylor, E.W., Conlon, J.M., Wang.. T., 2005. Hemodynamic effects of python neuropeptide gamma in the anesthetized python, Python regius. Regul. Pept. 18, 15-26), rattlesnakes (Galli, G., Skovgaard, N., Abe, A.S., Taylor, E.W., Wang, T., 2005. The role of nitric oxide in the regulation of the systemic and the pulmonary vasculature of the rattlesnake, Crotalus durissus terrificus. J. Comp. Physiol. 175B, 201-208) and turtles (Crossley, D.A., Wang, T., Altimiras, J., 2000. Role of nitric oxide in the systemic and pulmonary circulation of anesthetized turtles (Trachemys scripta). J. Exp. Zool. 286, 683-689). These five species of reptiles possess different combinations of division of the heart and structural complexity of the lungs. Comparison of their responses to NO donors and NOS inhibitors may reveal whether the potential contribution of NO to vascular tone correlates with pulmonary complexity and/or with blood pressure. All existing studies oil reptiles have clearly established a potential role for NO in regulating vascular tone in the systemic circulation and NO may be important for maintaining basal systemic vascular tone in varanid lizards, pythons and turtles, through a continuous release of NO. In contrast., the pulmonary circulation is less responsive to NO donors or NOS inhibitors, and it was only in pythons and varanid lizards that the lungs responded to SNP. Both species have a functionally separated heart, so it is possible that NO may exert a larger role in species with low pulmonary blood pressures, irrespective of lung complexity. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: nitric oxide; L-NAME; reptiles; Varanus; Trachemys; Python; Crotalus; cardiovascular; local regulation; blood pressure; blood flow